ẢNH HƯỞNG CỦA MỘT SỐ ANION ĐẾN KHẢ NĂNG BẢO VỆ CHỐNG ĂN MÒN CỦA MÀNG POLYPYROL TỔNG HỢP ĐIỆN HÓA TRONG DUNG DỊCH TETRAOXALAT - Giang, Đỗ Xuân; Lê Hiền, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
Polypyrrole (Ppy) films containing large anions have been studied as protective coating for carbon steel. In this work, the large ions such as anions surfactants (dodecylsulfate, dodecyl benzene sulfonate), polyanions (polystyrenesulfonate) and anions inhibitors (amino tris-metylenphosphonic acid) have been added in Ppy synthesis solution containing 0.05 M potassium tetraoxalate and 0.1 M pyrrole. The influence of theirs nature and concentration on Ppy synthesis process, electrochemical behaviors and protection time by the films obtained have been also investigated in detail.